(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
The main objective of this study is to enhance the poor performance of oil well cement in terms of mechanical properties by using pure polypropylene fibers. Polypropylene fibers were added in increasing concentrations from 0 to 0.1%, 0.3%, 0.5%, 0.7%, and 0.9% by weight of cement (BWOC). Rheological parameters, density, fluid loss, permeability, porosity, compressive strength, tensile strength, and flexural strength were all tested. A new method for measuring the tensile strength of cement samples in the presence of a casing is also evaluated in this research. In addition, the interfacial bonding shear strength, which represents the strength of cement adhesion to the casing, was measured using a new laboratory procedure. The influence of adding polypropylene fibers on rheology, density, and fluid loss can be ignored, according to the results of the experiments. The permeability and porosity of cement samples increased as the proportion of polypropylene fibers increased, according to the findings. Further, an increase in polypropylene fibers concentration up to 0.3%BWOC led to improving the mechanical properties at different curing times. The bonding strength of the casing cement interface improved with increasing polypropylene fibers concentration up to 0.5% BWOC.